Moral hypocrisy, power and social preferences - Aldo Rustichini; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2012)
We show with a laboratory experiment that individuals adjust their moral principles to the situation and to their actions, just as much as they adjust their actions to their principles. We first elicit the individuals' principles regarding the fairness and unfairness of allocations in three different scenarios (a Dictator game, an Ultimatum game, and a Trust game). One week later, the same individuals are invited to play those same games with monetary compensation. Finally in the same session we elicit again their principles regarding the fairness and unfairness of allocations in the same three scenarios. Our results show that individuals adjust abstract norms to fit the game, their role and the choices they made. First, norms that appear abstract and universal take into account the bargaining power of the two sides. The strong side bends the norm in its favor and the weak side agrees: Stated fairness is a compromise with power. Second, in most situations, individuals adjust the range of fair shares after playing the game for real money compared with their initial statement. Third, the discrepancy between hypothetical and real behavior is larger in games where real choices have no strategic consequence (Dictator game and second mover in Trust game) than in those where they do (Ultimatum game). Finally the adjustment of principles to actions is mainly the fact of individuals who behave more selfishly and who have a stronger bargaining power. The moral hypocrisy displayed (measured by the discrepancy between statements and actions chosen followed by an adjustment of principles to actions) appears produced by the attempt, not necessarily conscious, to strike a balance between self-image and immediate convenience.
urn:nbn:de:101:1-201303221788
Keywords: D03; D63; C91; C7; 330; moral hypocrisy; fairness; social preferences; power; self-deception; Spieltheorie; Verhandlungstheorie; Soziale Norm; Gerechtigkeit; Verhandlungsmacht; Test